Retinal microcirculation and leukocyte telomere length in the general population - Dries S. Martens (Nature Portfolio, 2018)
Abstract Retinal arteriolar narrowing increases with age and predict adverse cardiovascular outcomes. Telomere length keeps track of the division of somatic cells and is a biomarker of biological age. We investigated to what extent retinal arteriolar diameters are associated with biological age, as captured by leukocyte telomere length (LTL). In 168 randomly selected Flemish participants from the family-based population study FLEMENGHO (mean age, 46.2 years) at baseline, of whom 85 underwent a follow-up examination (median, 4.1 years), we post-processed nonmydriatic retinal photographs and measured LTL. In men only, central retinal arteriolar equivalents (CRAE) and arteriole-to-venule ratio (AVR) were associated with LTL with stronger associations at higher age and body mass index. In men aged 57.6 years (75th percentile) a 20% shorter LTL was associated with a decrease in CRAE of 4.57 µm. A 20% shorter LTL was associated with a decrease of 5.88 µm in CRAE at a BMI of 29.9 kg/m2 (75th percentile). Similar associations were observed between AVR and LTL. In women, no retinal microvascular traits were associated with LTL. Retinal arteriolar narrowing in men but not in women is associated with biological age. Our findings support the idea that avoiding overweight contributes to maintaining a healthier microcirculation.